1988
DOI: 10.1002/eji.1830180308
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human granulocyte‐macrophage colony‐stimulating factor induces secretion of autoinhibitory monokines by U‐937 cells

Abstract: Colony-stimulating factors are required for survival proliferation, differentiation and functional activation of granulocytes, macrophages and their precursor cells. In the present report, however, we demonstrate antiproliferative activity of recombinant human (rh) granulocyte-macrophage colony-stimulating factor (GM-CSF) on monoblast cell line U-937 and provide evidence for the involvement of tumor necrosis factor alpha TNF-alpha and interleukin 1 beta (IL 1 beta) in its growth inhibitory action. GM-CSF (but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

1991
1991
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…This was not possible with 17% FCS (Spinner et al (1995). In addition, U-937 cells that respond to rhG-CSF treatment (Lindemann et al, 1988) were a good systemic indicator (Fig. 2).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This was not possible with 17% FCS (Spinner et al (1995). In addition, U-937 cells that respond to rhG-CSF treatment (Lindemann et al, 1988) were a good systemic indicator (Fig. 2).…”
Section: Discussionmentioning
confidence: 93%
“…certainly important parameters for this clinically relevant topic. The presence of wild-type G-CSF receptor does not necessarily mean proliferation of cancer cells since an inhibition of proliferation has been observed for the ovarian cancer cell line NIH: OVCAR-3 (Spinner et al, 1995;Conner et al, 1994) and the leukemic cell line U-937 (Lindemann et al, 1988). Transfection of the murine G-CSF receptor-negative cell line WEHI-3B with wild-type G-CSF receptor causes differentiation of this cell line in response to exogenous G-CSF (Li et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that exogenous TNF-a up-regulates in vitro expression of TNF-a and EGFR in human pancreatic carcinoma cells (Schmiegel et al, 1993). Interestingly, ZL34 cells produce TNF-a (our own observation) as well as granulocyte-macrophage colony-stimulating factor (GM-CSF) (Schmitter et al, 1992), which is known as an activator of TNF-a production (Lindemann et al, 1988). Moreover ZL34 cells secrete interferon-y (our own observation), a cytokine which also enhances TGF-a expression (Hamburger & Pinnamaneni, 1993).…”
Section: Cell Cultures and Media Conditioningmentioning
confidence: 67%